Segmentation des images par algorithme de classification (supervisée ou non supervisée) - Rafika, Lassoued; Chaima, Ahmouda; Kenza, Sedouga (university of eloued جامعة الوادي, 2018)
یتناول ھذا المشروع أحد الجوانب الرئیسیة في مجال معالجة الصور الرقمیة: تجزئة الصورة حسب التصنیف. على الرغم من تطور ھذه التقنیة والنھج المتعدد التخصصات المستخدم للوصول إلیھا ، ھناك دائمًا مشكلات تجزئة الصورة لأن الصورة نفسھا ھي كائن معقد مقارنة بالبیانات الأخرى. طبقنا تقسیم K- : الصور بشكل عام(صور ملونة)، بناء على واحدة من خوارزمیات التصنیف غیر الخاضعة للرقابة باستخدام NetBeans Object Oriented بسبب بساطتھا وكفاءتھا وسرعتھا. لقد اخترنا بیئة . means بدقة أكبر.This project addresses one of the main aspects in the field of digital image processing: image segmentation by classification. Despite the evolution of this technology and the multidisciplinary approach used to achieve it ,there are still problems of fragmentation of the image because the image itself is a complex object compared to other data. We applied image segmentation in general (color image), based on one of the unsupervised classification algorithms: K-means. Because of its simplicity, efficiency and speed. We chose a NetBeans object-oriented environment using more precisely the JAVA programming language.
licence mémoire informatique
Keywords: تصنیف الصور, تجزئة الصور , التصنیف الخاضع للرقابة , التصنیف الغیر خاضع . K-means, للرقابة ,خوارزمیات التصنیف ,تجزئة الصور; Image Classification, Supervised Classification, Unsupervised Classification, Classification Algorithms, Image Segmentation, K-means.